Applying an ontology on data integration - Buccella, Agustina (2003)
The term “Federated Databases” refers to the data integration of distributed, autonomous and heterogeneous databases. However, a federation can also include information systems, not only databases. When integrating data, several issues must be addressed. Here, we focus on the problem of heterogeneity, more specifically on semantic heterogeneity – that is problems related to semantically equivalent concepts or semantically related/unrelated concepts. In order to address this problem, we apply the idea of ontologies as a tool for data integration. In this paper, we explain this concept and we briefly describe a method for constructing an ontology by using a hybrid ontology approach.